Management of Failed Spinal Anesthesia - Hastuti, Wiji; Fajar Apsari, Ratih Kumala; Sudadi, Sudadi (Jurnal Komplikasi Anestesi, 2025)
The management of failed spinal anesthesia is a significant challenge in surgical procedures. Spinal anesthesia failure can occur either partially or totally, often leading to conversion to general anesthesia, which adds clinical risks and potential complications. The aim of this study is to evaluate the factors contributing to spinal anesthesia failure and identify effective management strategies. The study found that factors such as patient positioning, anesthesiologist experience, the number of attempts, and patient BMI significantly influenced spinal block success. Total spinal anesthesia failure often requires conversion to general anesthesia, whereas partial failures can be managed with adjuvant medications or repeated procedures. Understanding the management of failed spinal anesthesia is essential for providing safe and effective care